The Political Economy of Salt Imports in Indonesia - Beltahmamero Simamora; Marlina Deliana; Syafruddin Ritonga (Polit Journal Scientific Journal of Politics, 2021)
The use of salt is wide, including in the chemical industry, various foods and beverages, pharmaceuticals and cosmetics. The decision to import salt is aimed at protecting the sustainability of production in the national industrial sector. Government Regulation Number 9 of 2018 was issued without involving the Ministry of Marine Affairs and Fisheries (KKP). The PP for Salt Imports removes the authority of the KKP in providing recommendations for importing industrial salt. The salt import made by the government has received legitimacy from the Ministry of Industry because it is seen as being able to increase investment and welfare for the community. However, the import of salt do not have to get recommendations from the Ministry of Marine Affairs and Fisheries are a blunder for the government. Because it is very contrary to the constitution. The concepts presented by Thomas Oatley, namely interests, political institutions and Helen V. Milner, namely Interest, Institutions, and Information, are used to analyze salt import policies. 100 percent of industrial salt is still imported, because Indonesia unable to produce salt for industrial needs. Thus, in terms of the political economy of salt business, it can be concluded that the recurring issue of salt scarcity has been caused by serious errors in the political economy of the salt business in Indonesia. This mistake, objectively, can be traced from the behavior of salt business players and the government to reform for a better Indonesian salt business. 100 percent of industrial salt is still imported, because Indonesia unable to produce salt for industrial needs. Thus, in terms of the political economy of salt business, it can be concluded that the recurring issue of salt scarcity has been caused by serious errors in the political economy of the salt business in Indonesia. This mistake, objectively, can be traced from the behavior of salt business players and the government to reform for a better Indonesian salt business. 100 percent of industrial salt is still imported, because Indonesia unable to produce salt for industrial needs. Thus, in terms of the political economy of salt business, it can be concluded that the recurring issue of salt scarcity has been caused by serious errors in the political economy of the salt business in Indonesia. This mistake, objectively, can be traced from the behavior of salt business players and the government to reform for a better Indonesian salt business.